Doped Layered Double Hydroxides for Efficient Hydrogen Evolution Reaction - Phagami, Jenisha; Koirala, Pragya; Oli, Diksha; Bhatta, Bismita; Swarnakar, Komal; Karki, Bishow; Chaudhari, Ashim; Ghimire, Muskan; Kandel, Mani Ram (Journal of Nepal Chemical Society, 2026)
Hydrogen is considered a primary solution to meet the global energy demand of the present and future generations, as it is clean and renewable. To produce hydrogen efficiently and cost-effectively, layered double hydroxide (LDH)-based electrocatalysts have been widely employed to enhance the hydrogen evolution reaction (HER). In this study, a hybrid bimetallic iron–cobalt–layered double hydroxide (Fe–Co–LDH) synthesized on a clean nickel foam (NF) substrate to develop an active electrocatalyst for HER. In an alkaline medium, the Fe–Co–LDH/NF electrocatalyst delivered low overpotentials of 175 mV at 10 mA cm⁻² and 238 mV at 50 mA cm⁻², and the Tafel slope of 91 mV dec⁻¹. The high activity is attributed to the synergistic effect of Fe and Co, the layered structure providing abundant active sites, good electrical conductivity, and strong metal–hydroxide interactions facilitating water dissociation. These findings suggest that the synthesized Fe–Co–LDH electrocatalyst holds great promise for efficient HER.